2006
DOI: 10.1542/peds.2006-0815
|View full text |Cite
|
Sign up to set email alerts
|

Examining Characteristics and Associated Distress Related to Internet Harassment: Findings From the Second Youth Internet Safety Survey

Abstract: Internet harassment can be a serious event for some youth. Because there has been a significant increase in the prevalence of Internet harassment from 2000 to 2005, adolescent health professionals should continue to be vigilant about such experiences in the lives of young people with whom they interact. Social problems and online aggressive behavior are each associated with elevated odds of being the target of harassment. Thus, prevention efforts may be best aimed at improving the interpersonal skills of young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
266
1
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(298 citation statements)
references
References 13 publications
12
266
1
19
Order By: Relevance
“…Ybarra et al (2006) support findings with their own findings that with traditional bullying, boys are more likely to bully than girls, however with online bullying, the incidents are equal. Boys are as likely as girls to bully others online.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Ybarra et al (2006) support findings with their own findings that with traditional bullying, boys are more likely to bully than girls, however with online bullying, the incidents are equal. Boys are as likely as girls to bully others online.…”
Section: Introductionsupporting
confidence: 83%
“…Boys are as likely as girls to bully others online. Data from the Second Youth Internet Safety Study (YISS-2, a national survey of 1,500 households of youth between the ages to 10-17) by Ybarra et al (2006) showed that 1 in 3 youth reported that they had harassed someone online at last once in the previous year. Of the youth who said they harassed someone online, 82% said that someone else had said mean or hurtful things about them online.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research consistently describes adverse consequences of cyber-aggression, including problem behavior, depressed mood, and lowered self-esteem (e.g. Ybarra et al, 2007;Ybarra & Mitchell, 2004a;Ybarra et al, 2006). However, no research to date has examined how the developmental course of these risks relates to subsequent perpetration and victimization of cyber-aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, cyber-aggression perpetration is linked with a higher prevalence of problem behaviors such as physical aggression and damaging property (Ybarra & Mitchell, 2004a), and perpetration and victimization are related to frequent substance use and delinquency (Hinduja & Patchin, 2007;Ybarra & Mitchell, 2004b). Finally, there is an apparent link between cyber-aggression and poor mental health, including lowered self-esteem (Brighi, et al, 2012;Patchin & Hinduja, 2010) and elevated depressive symptoms (Wang, Nansel, & Iannotti, 2011;Ybarra & Mitchell, 2004b;Ybarra, Mitchell, Wolak, & Finkelhor, 2006). For victims, this extends to psychosomatic difficulties (Sourander, et al, 2010) including adjustment issues such as higher feelings of loneliness from parents and peers (Brighi, et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that online and offline victimisation were often combined for youth in general [10,11]. A recent meta-analysis showed that sexual-minority youth were on average more likely to experience sexual abuse (OR 3.9), parental physical abuse (OR 2.3), peer assault at school (OR 2.7) or to miss school through fear (OR 3.9) [12].…”
Section: Introductionmentioning
confidence: 99%